2019
DOI: 10.1371/journal.pone.0210427
|View full text |Cite
|
Sign up to set email alerts
|

The lifetime prevalence of hospitalised head injury in Scottish prisons: A population study

Abstract: BackgroundThere is mounting evidence that associates brain injury and offending behaviour, and there is a need to understand the epidemiology of head injury in prisoners in order to plan interventions to reduce associated disability and risk of reoffending. This is the first study to determine the lifetime prevalence of hospitalised head injury (HHI) in a national population of current prison inmates. In addition characteristics of prisoners with HHI and were compared to prisoners without HHI to discover wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…Nine of the twelve studies investigated adults in prison and three, juveniles in prison (27)(28)(29). One was a national prison population study that included adults and juveniles (4). One further study included adults and a single juvenile prisoner; only the adult data were considered in this review (30; see table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine of the twelve studies investigated adults in prison and three, juveniles in prison (27)(28)(29). One was a national prison population study that included adults and juveniles (4). One further study included adults and a single juvenile prisoner; only the adult data were considered in this review (30; see table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Moderate-severe HI (LoC > 30 minutes) was reported as 22% and 37% in two adult studies (32,34) and 12.5% in one juvenile study (28). Another considered lifetime hospital admissions with HI in the population of females in Scotland who were under the age of 36 years and in prison (n=248) using ICD codes, and reported a HI prevalence of 19% (4).…”
Section: Methods For Assessing the Prevalence Of Hi In Female Offendersmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence relating to abnormal moral development and sociopathic patterns of behavior after injury to the vmPFC in childhood may explain why such a high number of offenders in custody have a history of head/brain injury. Williams (163) reported prevalence rates for TBI in young incarcerated male offenders (average age 16 years) as high as 60%, while McMillan et al (164) recently found that the prevalence of hospitalized head injury in prisoners (24.7 per cent; 1080/4,374) was significantly higher than a matched general population sample (18.2 per cent; 2394/13122). In a systematic review of youth offending, Hughes et al (165) reported prevalence rates of brain injury amongst incarcerated youth of between 16.5 and 72.1 per cent.…”
Section: Failure Of Moral Development and Risk Of Offender Behaviormentioning
confidence: 99%